1996
DOI: 10.1007/bf00573851
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcome of hydrocephalus following intra-/periventricular hemorrhage in preterm infants: short- and long-term results

Abstract: Over a 5-year period (1984-1988) intra- and periventricular hemorrhage (IVH/PVH) was observed in 299 preterm infants. Sixty-eight infants developed posthemorrhagic hydrocephalus (PH); of these, 23 infants died and 40 infants could be followed up for assessment of neurological development (5 patients were lost to follow-up). At 1 year of corrected age 15% (25% at 5 year follow-up) of the infants were determined to have developed normally, 35% (25% at 5-year follow-up) showed mild neurological symptoms and/or sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…The gestational age-specific prevalence of hydrocephalus during the same period increased particularly in children born extremely preterm, with a concomitant decrease in perinatal mortality of the same magnitude. As a result, although children born extremely preterm nowadays have a better chance of survival, they run the risk of a perinatal intracerebral haemorrhage, in some cases leading to hydrocephalus and often to other neurological impairments (Futagi et al 2005, Resch et al 1996. The prevalence of hydrocephalus in children born at term decreased at the beginning of the nineties but has since remained fairly stable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gestational age-specific prevalence of hydrocephalus during the same period increased particularly in children born extremely preterm, with a concomitant decrease in perinatal mortality of the same magnitude. As a result, although children born extremely preterm nowadays have a better chance of survival, they run the risk of a perinatal intracerebral haemorrhage, in some cases leading to hydrocephalus and often to other neurological impairments (Futagi et al 2005, Resch et al 1996. The prevalence of hydrocephalus in children born at term decreased at the beginning of the nineties but has since remained fairly stable.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have confirmed the risk of a poor outcome in children with a peri-or postnatal cause vs. a prenatal origin of the hydrocephalus (Casey et al 1997, HoppeHirsch et al 1998, Mirzai et al 1998, Resch et al 1996. In particular, children born very or extremely preterm with post-haemorrhagic hydrocephalus run a high risk of associated neuroimpairments.…”
Section: Fig 7 Newborn Children With Neural Tube Defects (Ntd) (Anenmentioning
confidence: 93%
“…7,43 Avoiding multiple shunt infections and surgical revisions should be a primary objective in infants with hydrocephalus, as they have been shown to correlate with a worse neurocognitive outcome. 31,37 Furthermore, several authors have shown that in the absence of raised intracranial pressure, ventriculomegaly does not impair neurodevelopment. 15,54 This is supported by Warf et al, who demonstrated comparable neurocognitive outcomes in hydrocephalic MMC children undergoing ETV/CPC or CSF shunting.…”
Section: Defining Successmentioning
confidence: 99%
“…Very low birth weight infants are at high risk of developing IVH (1). PHH is a major complication of IVH and contributes importantly to subsequent long-term cognitive and motor disability (2)(3)(4)(5). The management of infants with PHH is controversial because the benefits of any specific treatment regimen have not been established (2,(5)(6)(7)(8).…”
mentioning
confidence: 99%